PENGELOLAAN LABORATORIUM FISIKA DASAR DALAM MENUNJANG KINERJA DAN KEPUASAN PENGGUNA LABORATORIUM FISIKA FKIP UNIVERSITAS JEMBER - Emilia Anies; Subiki subiki; Trapsilo prihandono (FKIP Universitas Jember, 2017)
Laboratory’s management is the important thing for a laboratory. Good management of laboratory will influence the users’ performance. Good management need good performance of laboratory’s manager. Purposes of this study were to describe how well the basic physics laboratory’s management was done and how its influence to users’ performance dan satisfaction that was caused by laboratory manager’s performance when she was serving users. The analysis was conducted by using descriptive qualitative methods. The results showed that basic physics laboratory of FKIP in Jember University was in good category but for maintenance and safety need to be better, students’ performance as users in very good category although lecturers’ performance as users were in good category, and students and lecturers’ satisfaction when they’re served by laboratory’s manager in some performance’s indicators such as reability, responsiveness, emphaty, assurance and tangible were in a good enough category.